Pemanfaatan E-Commerce Dan Rebranding Produk Guna Meningkatkan Pendapatan Pada UMKM Gudeg Blitar Di Kelurahan Kepanjenlor Kota Blitar - Raihan Izzul Bassam Romadhoni; Ririt Iriani Sri S; Mohammad Wahed (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
In the era of the fourth industrial revolution, the rapid advancement of information technology has a significant impact on society in supporting various business activities, both on a large and small scale, with the aim of gaining global recognition for businesses. The development of information technology also contributes to increasing sales volume and profits. It is expected that the use of internet technology will provide significant benefits for the competitive business world. The success of companies in this business competition depends on their ability to implement technology and information in their operations. One effective way to enhance business competition and product sales is through the adoption of electronic technology, such as e-commerce, to market various products or services in physical and digital forms. This research aims to optimize the utilization of digital marketing for Gudeg Blitar's small and medium enterprises (MSMEs). The research utilizes a mentoring method, involving several stages such as observation, planning, implementation, and evaluation. In the data collection process, the researcher conducted direct interviews with MSMEs owners located in Kepanjen Lor Village, Blitar City. The findings of this research indicate that by selecting the appropriate social media platforms and optimizing the use of e-commerce, sales can be increased